Determination of the critical mixing intensity for secondary nucleation of paracetamol in an oscillatory flow crystallizer - P. Cruz (2018)
A simple approach was employed to determine the critical mixing intensity for secondary nucleation of paracetamol, Re-o(c), in an oscillatory flow crystallizer, i.e., the mixing intensity at which the transition from crystal growth to secondary nucleation control of crystal size occurs. Re-o(c) was determined for different initial supersaturations as a break in the trend of increasing crystal size with mixing intensity by performing several seeded batch experiments at different oscillation frequencies. It was found that Re-o(c) is high and virtually constant at low initial supersaturations and decreases when supersaturation increases. This parameter has a great influence on crystal growth rate and, consequently, on crystal size. Since larger particles offer greater collision success for attrition than small ones and contact nucleation is favored by high supersaturations, a lower mixing intensity level is required to reach the limit for secondary nucleation control under higher levels of supersaturation. The placement of the limit for secondary nucleation control in a real crystallization environment makes it possible to predict the system behavior under certain operating conditions.